A COMPARISON OF TWO METHODS TO SEGMENT BONE EROSIONS IN THE METACARPOPHALANGEAL JOINTS OF RHEUMATOID ARTHRITIS PATIENTS - Figueiredo, C.; Simon, David; Stemmler, F.; Weißenfels, Anja; Weishäupl, Dirk; Museyko, Oleg; Friedberger, Andreas; Rech, Jürgen; Hueber, Axel; Haschka, J.; Schett, Georg; Engelke, Klaus; et al. (2016)
EVALuna2:13471

An overview of physical activity referral schemes worldwide and their key interventional components - Mino, Eriselda; Hanson, Coral; Geidl, Wolfgang; Naber, Inga; Weißenfels, Anja; Mchale, Sheona; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (European Society of Cardiology (ESC), 2022)

Are physical activity referral scheme components associated with increased physical activity, scheme uptake, and adherence rate? A meta-analysis and meta-regression - Mino, Eriselda; Pfeifer, Klaus; Hanson, Coral L.; Schuler, Michael; Brandmeier, Anna; Klamroth, Sarah; Naber, Inga; Weißenfels, Anja; McHale, Sheona; Abu-Omar, Karim; Gelius, Peter; Whiting, Stephen; et al. (International Journal of Behavioral Nutrition and Physical Activity, 2024)
Background: Physical activity referral schemes (PARS) are composed of various components, such as a written prescription or a person-centered approach. The role of these components in their effectiveness is yet to be understood. Therefore, we aimed to explore the relationships between PARS components and physical activity, scheme uptake, and adherence rate; and to estimate the effect of PARS. Methods: We searched Scopus, PubMed, Web of Science, CINAHL, ScienceDirect, SpringerLink, HTA, Wiley Online Library, SAGE Journals, Taylor & Francis, Google Scholar, OpenGrey, and CORE. Eligible studies were published between 1990 and November 2023 in English or German, investigated PARS with participants aged ≥ 16 years, and reported physical activity, scheme uptake, or scheme adherence. Separate random-effects meta-analysis by comparison group were conducted for physical activity. Scheme uptake and adherence rates were pooled using proportional meta-analysis. The components were analyzed via univariate meta-regression. We rated the risk of bias using RoB2 and ROBINS-I, and the certainty of evidence using GRADE. Results: Fifty-two studies were included. PARS were more effective in increasing physical activity than usual care (k = 11, n = 5046, Hedges’ g = 0.18, 95%CI 0.12 to 0.25; high certainty of evidence). When PARS were compared with physical activity advice or enhanced scheme versions, the pooled Hedges’ g values for physical activity were -0.06 (k = 5, n = 1082, 95%CI -0.21 to 0.10; low certainty of evidence), and 0.07 (k = 9, n = 2647, 95%CI -0.03 to 0.18; low certainty of evidence) respectively. Scheme uptake was 87% (95%CI 77% to 94%, k = 14, n = 5000) across experimental studies and 68% (95%CI 51% to 83%, k = 14, n = 25,048) across non-experimental studies. Pooled scheme adherence was 68% (95%CI 55% to 80%, k = 16, n = 3939) and 53% (95%CI 42% to 63%, k = 18, n = 14,605). The meta-regression did not detect any significant relationships between components and physical activity or scheme uptake. A person-centered approach, screening, and brief advice were positively associated with scheme adherence, while physical activity sessions were negatively associated. Conclusion: PARS are more effective in increasing physical activity than usual care only. We did not identify any components as significant predictors of physical activity and scheme uptake. Four components predicted scheme adherence, indicating that the component-effectiveness relationship warrants further research.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Exercise prescription; Exercise referral scheme; Physical activity; Physical activity prescription; Physical activity referral scheme; Referral and consultation

A systematic review and narrative synthesis of physical activity referral schemes’ components - Mino, Eriselda; Hanson, Coral L.; Naber, Inga; Weißenfels, Anja; Mchale, Sheona; Saftig, Jane; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Whiting, Stephen; Wickramasinghe, Kremlin; Galea, Gauden; et al. (International Journal of Behavioral Nutrition and Physical Activity, 2023)
Background Physical activity referral schemes (PARS) are complex multicomponent interventions that represent a promising healthcare-based concept for physical activity (PA) promotion. This systematic review and narrative synthesis aimed to identify the constitutive components of PARS and provide an overview of their effectiveness. Methods Following a published protocol, we conducted a systematic search of PubMed, Scopus, Web of Science, CINAHL, ScienceDirect, SpringerLink, HTA, Wiley Online Library, SAGE Journals, Taylor & Francis, Google Scholar, OpenGrey, and CORE from 1990 to January 2023. We included experimental, quasi-experimental, and observational studies that targeted adults participating in PARS and reported PA outcomes, scheme uptake, or adherence rates. We performed an intervention components analysis using the PARS taxonomy to identify scheme components and extracted data related to uptake, adherence, and PA behavior change. We combined these to provide a narrative summary of PARS effectiveness. Results We included 57 studies reporting on 36 PARS models from twelve countries. We identified 19 PARS components: a patient-centered approach, individualized content, behavior change theory and techniques, screening, brief advice, written materials, a written prescription, referral, baseline and exit consultation, counselling support session(s), PA sessions, education session(s), action for non-attendance, structured follow-up, a PA network, feedback for the referrer, and exit strategies/routes. The PARS models contained a mean of 7 ± 2.9 components (range = 2–13). Forty-five studies reported PA outcome data, 28 reported uptake, and 34 reported adherence rates. Of these, approximately two-thirds of studies reported a positive effect on participant PA levels, with a wide range of uptake (5.7–100.0%) and adherence rates (8.5–95.0%). Conclusions Physical activity referral scheme components are an important source of complexity. Despite the heterogeneous nature of scheme designs, our synthesis was able to identify 19 components. Further research is required to determine the influence of these components on PARS uptake, adherence, and PA behavior change. To facilitate this, researchers and scheme providers must report PARS designs in more detail. Process evaluations are also needed to examine implementation and increase our understanding of what components lead to which outcomes. This will facilitate future comparisons between PARS and enable the development of models to maximize impact.
Keywords: physical activity; physical activity referral scheme; physical activity on prescription

Aufbau eines Interventionskonzeptes zur Förderung der bewegungsbezogenen Gesundheitskompetenz in der Gesundheitsversorgung - Naber, Inga; Klamroth, Sarah; Weißenfels, Anja; Geidl, Wolfgang; Mino, Eriselda; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Jahrestagung dvs-Kommission Gesundheit, 2022)
Einleitung Für die Bewegungsförderung von Menschen mit nichtübertragbaren Erkrankungen (non-communicable diseases – NCD) kann die ärztlich-initiierte Verordnung von körperlicher Ak-tivität als wirksame Methode eingesetzt werden. Wird dabei zudem die bewegungsbezo-gene Gesundheitskompetenz (BGK) gefördert, so sind positive Effekte auf das Bewegungs-verhalten zu erwarten. Entsprechend wurde im Rahmen des Forschungsprojektes Bewegt-Versorgt eine ärztlich-initiierte Bewegungsversorgungskette entwickelt, dessen Kernkompo-nente eine BGK-basierte individuelle Bewegungsförderung (IBF) zur Umsetzung in der Ge-sundheitsversorgung darstellt. Die Entwicklung und Gestaltung der IBF soll im vorliegenden Beitrag vorgestellt werden. Methode Die IBF wurde in enger Zusammenarbeit mit Projektpartnerinnen und -partnern aus dem Bereich der Bewegungsförderung entwickelt. Hierfür wurden a) evidenzbasierte Methoden und Inhalte aus anderen Studien sowie theoretische Grundgedanken zur Bewegungsförde-rung berücksichtigt. Dabei erfolgte eine Orientierung am BGK-Modell sowie an Rahmenkon-zepten zur Entwicklung von verhaltensbezogenen Interventionsprogrammen (u.a. Interven-tion Mapping, Techniken zur Verhaltensänderung). Die selektierten Inhalte und Methoden wurden b) von Expertinnen und Experten aus Forschung und Praxis besprochen und adap-tiert. Anschließend wurden c) die festgelegten inhaltlichen und methodischen Elemente in ein modulares Konzept transferiert und durch Arbeitsmaterialien ergänzt. Ergebnisse Das modulare Interventionskonzept der IBF integriert BGK-spezifische Inhalte und umfasst eine 1:1 Betreuung durch geschultes Bewegungsfachpersonal über einen Zeitraum von 24 Wochen (6 Einheiten à 60 Minuten, 3 Assessments). Basierend auf den jeweiligen Voraus-setzungen, Bedürfnissen und Präferenzen der Teilnehmenden werden verschiedene Bewe-gungsformen ausprobiert und ein individuell angepasster Bewegungsplan entwickelt. Wäh-rend der IBF wird durch die gezielte Unterstützung bei der Handlungsplanung und bei der Kontaktaufnahme mit Bewegungsanbietern die Überführung in eigenständige körperliche Aktivität angestrebt. Diskussion Im Rahmen eines Modellvorhabens nach §§ 63 Abs. 2, 64 SGB V wird die IBF derzeit in der Gesundheitsversorgung erprobt. Hier wird sich zeigen, inwieweit das Interventionskonzept wie geplant umgesetzt werden kann und wie wirksam es in Hinblick auf die Steigerung der körperlichen Aktivität und der BGK ist.<br
Keywords: körperliche Aktivität; bewegungsbezogene Gesundheitskompetenz

BewegtVersorgt - Bewegungsförderung im Gesundheitssystem - Weißenfels, Anja (2021)

BewegtVersorgt: co-development of a physical activity referral scheme for use in the German healthcare system - Mino, Eriselda; Naber, Inga; Weißenfels, Anja; Klamroth, Sarah; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (20. Deutscher Kongress für Versorgungsforschung, 2021)
Background and status of (inter)national research: Physical activity referral schemes (PARSs) are a well-known method of promoting physical activity among the inactive primary care population with or at risk of developing non-communicable diseases. Despite significant expansion throughout Europe, a national scheme has not yet been established in Germany. Thus, similar efforts were initiated in June 2019 through the BewegtVersorgt project. Objectives: To design a PARS model with the premise of future integration into the German healthcare system. Methods: A co-production approach, including scenario thinking elements and cooperative planning, was utilized to develop the PARS. The research team worked closely together with twelve organizations from various sectors - health insurances, physicians, physiotherapists, sports, and patient organizations. Twelve bilateral meetings were conducted from June to September 2019, with the stakeholders exploring their PARS vision. These were followed by three half-day co-production meetings held in presence, which took place from October 2019 until January 2020. Successive negotiation meetings were organized to refine and finalize the co-developed work. The final PARS was held forward for approval by the end of 2020 in an online stakeholder meeting. Results: The co-produced PARS starts with the primary care physician, as the gatekeeper in the German healthcare system, who offers 10 min physical activity advice to the patients who would benefit from physical activity participation. Afterward, the patients are referred to an exercise professional through a referral form. The exercise professional delivers the remaining central components of the intervention - initial assessment, six 1-hour individual physical activity counseling sessions spread throughout 12 weeks, final assessment, a progress report to the general practitioner, and one follow-up visit at six months. The intervention uses a patient-centered approach and motivational interviewing. The end goal is an adaptation of an active lifestyle and transfers to local physical activity opportunities. Discussion: This PARS was comprehensively designed based on coordinated efforts from various areas of expertise. The involvement of key stakeholders ensured that the final PARS incorporates scheme providers, funders, and service-users perspectives. The combination of international scientific evidence and practical knowledge ensures higher feasibility and acceptability of the intervention. Practical implications: If proved efficacious, the successful integration of the PARS in routine practice will likely benefit the chronically ill population. Consequently, this would translate into favorable economic implications. Further, this PARS has implications for health and exercise professionals who contemplate integrating physical activity promotion and behavior change aspects into their care standards. Appeal to practice (science and/or care) in one sentence: This health insurance covered PARS presents an opportunity for inter-sectoral collaboration between sport/physical activity and healthcare professionals.

BewegtVersorgt: Entwicklung neuer Versorgungsstrukturen zur Bewegungsförderung mit Hilfe eines Co-Production Ansatzes - Klamroth, Sarah; Weißenfels, Anja; Mino, Eriselda; Naber, Inga; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (25. Sportwissenschaftlicher Hochschultag der Deutschen Vereinigung für Sportwissenschaft (dvs), 2022)

BewegtVersorgt: Projektvorstellung und erste Erkenntnisse - Weißenfels, Anja; Klamroth, Sarah; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Sports, Medicine and Health Summit 2023, 2023)

Bewegungsförderung im deutschen Gesundheitssystem – Vorstellung einer pragmatischen Studie im Cluster-Design - Weißenfels, Anja; Klamroth, Sarah; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (25. dvs-Hochschultag "Sport,Mehr & Meer - Sportwissenschaft in gesellschaftlicher Verantwortung", 2022)
Einleitung Die zunehmende Inaktivität in der Bevölkerung macht es erforderlich, dass gezielte Maßnahmen zur Bewegungsförderung zum festen Bestanteil der Gesundheitsversorgung werden, wie es international bereits etabliert ist. Mit der Implementierung solcher bewegungsbezogenen Versorgungsstrukturen im deutschen Gesundheitssystem setzt sich das Projekt BewegtVersorgt auseinander. Hierbei werden über einen ‚co-production‘ Ansatz gemeinsam mit Akteuren des Gesundheitssystems Versorgungsketten zur verhaltensbezogenen Bewegungsförderung für Menschen mit nichtübertragbaren chronischen Erkrankungen entwickelt hat, die anschließend direkt in der Regelversorgung implementiert, erprobt und evaluiert werden sollen. Die Kernkomponente ist eine enge Zusammenarbeit zwischen ärztlichem Fachpersonal und Bewegungsexperten. Die Ziele der pragmatischen Studie beziehen einerseits die Überprüfung der Wirksamkeit der entwickelten Versorgungskette (u. a. Veränderung der körperlichen Aktivität, bewegungsbezogenen Gesundheitskompetenzen, Lebensqualität) und andererseits auch deren Implementierung in die Routineversorgung ein. Methodik Die pragmatische Studie ist als cluster-randomisierte kontrollierte Studie (cRCT) geplant und umfasst zwei Interventionsgruppen. Während eine Gruppe eine Kombination aus ärztlicher Kurzberatung und individueller Bewegungsförderung durch geschultes Bewegungsfachpersonal erhält (physical activity referral scheme – PARS), bekommt die Vergleichsgruppe eine ärztliche Kurzberatung und Informationsmaterial zur eigenständigen körperlichen Aktivität (physical activity advice – PAA). Geplant ist ein cRCT, bei dem 24 ärztliche Praxen randomisiert den beiden Interventionsarmen zugeordnet werden und insgesamt 552 Teilnehmende rekrutieren, beraten und entsprechend ihrer Gruppenzugehörigkeit weiterleiten. Zur Beantwortung der Fragestellungen bedient man sich einem Hybrid II – Design, wobei die Wirksamkeit der Intervention verstärkt über standardisierte Fragebögen evaluiert wird, während der Implementierungserfolg u. a. mittels qualitativer Interviews der ausführenden Akteure untersucht werden soll. Diskussion Durch die gemeinsame Entwicklung mit Akteuren des Gesundheitssystems erhofft man sich eine größtmögliche Akzeptanz der neuen Versorgungsstruktur und eine nachhaltige Verankerung in der Gesundheitsversorgung. So wird die Studie durch die Zusammenarbeit mit Kostenträgern als Modellvorhaben nach §§ 63 Abs. 2, 64 SGB V implementiert, die Akteure erhalten eine Leistungsvergütung und bereits bestehende Abrechnungswege sowie Strukturen innerhalb der ärztlichen wie auch therapeutischen Einrichtungen werden integriert. <br
Keywords: Verhaltensbezogene Bewegungsförderung; Gesundheitsversorgung

Bewertung bestehender Versorgungsketten zur Bewegungsförderung im deutschen Gesundheitssystem - Naber, Inga; Weißenfels, Anja; Geidl, Wolfgang; Mino, Eriselda; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (20. Deutscher Kongress für Versorgungsforschung, 2021)
Hintergrund und Stand (inter)nationaler Forschung: Im internationalen Kontext sind Bewegungsversorgungsketten (BVKs) bereits erfolgreich in die Regelversorgung eingebettet (z.B. Schweden). Dies befürworten auch die nationalen Empfehlungen für Bewegung und Bewegungsförderung, um nachhaltig die steigende Inzidenz von körperlicher Inaktivität bei Menschen mit nichtübertragbaren Erkrankungen oder manifesten Risikofaktoren für diese zu reduzieren. Im deutschen Gesundheitssystem bestehen bereits BVKs, deren spezifischer Bezug zur verhaltensbezogenen Bewegungsförderung jedoch bisher noch nicht erforscht worden ist. Zielsetzung: Daher sollen die identifizierten ärztlich initiierten BVKs für Rehabilitationssport (RS), Funktionstraining (FT), Physiotherapie (PT) und Präventionsprogramme (PP) hinsichtlich einer nachhaltigen Bewegungsförderung analysiert werden. Methode: Auf Grundlage der Qualitätskriterien zur Konzipierung, Implementierung und Evaluation von Interventionen zur Bewegungsförderung wurden öffentliche Dokumente systematisch geprüft. Zur Bewertung der BVKs mussten die Qualitätskriterien thematisch angepasst und über eine Expertenbefragung validiert werden. Die Bewertung der identifizierten BVKs erfolgte über zwei unabhängige Wissenschaftler („0“ nicht bewertbar bis „3“ trifft voll zu). Im Fokus der Analyse standen die Interrater Reliabilität (Cohens Kappa k) sowie die Häufigkeiten der Bewertungsskala. Ergebnisse: Ausgehend von der Analyse zweier unabhängiger Wissenschaftler lag die Interrater Reliabilität k bei .89. Der Bereich Nachhaltigkeit wurde bei allen BVKs als sehr gut bewertet. In Kategorien wie Multidimensionalität, Ziele und Zielverhalten, Befähigung sowie Qualität der Evaluation wurden Komponenten der Bewegungsförderung dagegen nicht ausführlich beschrieben oder nicht erwähnt. Diskussion: Das Bewertungstool ließ eine Analyse der BVKs hinsichtlich bewegungsförderlicher Komponenten zu, welches zeigt, dass die analysierten Interventionen die Qualitätskriterien bereits in vielen Kategorien erfüllen. Herauszustellen ist jedoch, dass wesentliche Aspekte, insbesondere bei RS, FT und PT, auf Grund fehlender Informationen nicht bewertbar sind. Eine Anpassung der fehlenden oder ungenügenden Informationen würde das Gesamtbild komplementieren und nach erfolgreichem Transfer in die Praxis möglicherweise die Qualität der Versorgungswege steigern. Praktische Implikationen: Um körperliche Aktivität nachhaltig in der Gesellschaft zu verankern, scheint eine verhaltensbezogene Bewegungsförderung, die durch Ärzt*innen initiiert wird, großes Potenzial zu haben. Zur Umsetzung bedarf es jedoch Anpassungen in den bestehenden gesetzlichen Rahmen- sowie Schulungskonzepten oder einer Entwicklung neuer Ansätze mit verhaltensbezogenem Fokus. Appell für die Praxis: Die Entwicklung einer spezifischen Versorgungskette zur verhaltensbezogenen Bewegungsförderung sollte auf Basis aller analysierten Stärken und Schwächen bereits bestehender BVKs vorangetrieben werden.

Comparison of Whole-Body Electromyostimulation versus Recognized Back-Strengthening Exercise Training on Chronic Nonspecific Low Back Pain: A Randomized Controlled Study - Weißenfels, Anja; Wirtz, Nicolas; Dörmann, Ulrike; Kleinöder, Heinz; Donath, Lars; Kohl, Matthias; Fröhlich, Michael; von Stengel, Simon; Kemmler, Wolfgang (BioMed Research International, 2019)
Background. Low back pain (LBP) affects almost everyone at least once in their lifetime. Various meta-analyses show promising effects on pain reduction for conventional exercise. However, the lack of time and, especially for pain patients, a fear of movement ("kinesiophobia") as well as functional limitations often oppose participation in such activities. In contrast, the advantage of novel training technologies like whole-body electromyostimulation (WB-EMS) lies particularly in a joint-friendly, time-effective, and highly customized training protocol and might be an alternative option for LBP patients. A meta-analysis of individual patient data and a comparison of WB-EMS against a passive control group confirmed the proof principle. Thus, the aim of this randomized controlled trial is to compare WB-EMS with a recognized back-strengthening exercise protocol to determine the corresponding effects on chronic, nonspecific LBP in people suffering from this. Methods and Findings. This randomized, controlled multicenter study is focused on novel and time-effective training technologies and LBP. In this contribution, the focus is primarily on the comparison of WB-EMS against a comparable conventional exercise training (CT). One hundred ten nonspecific chronic LBP patients, 40-70 years old, were randomly allocated to the intervention arms (WB-EMS: 55 vs. CT: 55). Both groups completed a 12-week program (WB-EMS: 1 × 20 min/week vs. CT: 1 × 45 min/week) specifically dedicated to LBP. The selection of the content of the active control group was based on the principles of WB-EMS training, which uses electrical stimulation to train mainly strength and stabilization in a very short time. Exercises were similar in all groups, with the focus on strengthening and stabilizing the trunk. Outcome measures were assessed by a four-week pain diary (before and during the last four weeks of intervention) as well as an isometric maximum strength measurement of the trunk muscles at baseline and after 12 weeks of intervention. Primary study endpoint was average pain intensity at the lumbar spine. Secondary study endpoints were maximum isometric strength of the back and the abdominals. The mean pain intensity of LBP decreased significantly in both groups (WB-EMS: -22.3 ± 20.9% vs. CT: -30.2 ± 43.9%; p<0.001), however, without significant intergroup difference (p=0.160). A similar result was observed for "maximum isometric strength of trunk muscles." The increase in back strength (WB-EMS: 15.6 ± 24.9% vs. CT: 23.0 ± 30.9%) was highly significant in both groups (p=0.001), and similar changes were observed for the trunk flexors (WB-EMS: 17.6 ± 24.8% vs. CT: 18.1 ± 24.8%). Also, at the secondary endpoint, no significant difference in pairwise comparison was observed in both cases (extension: p=0.297; flexion: p=0.707). Conclusion. In summary, both, WB-EMS and conventional back-strengthening protocol are comparably effective in reducing nonspecific chronic LBP in this dedicated cohort. The result is particularly positive in terms of time effectiveness and offers an adequate alternative for people with limited time resources or other barriers to conventional training methods.
CRIS-Team Scopus Importer:2019-10-29

Competencies for health-enhancing physical activity are associated with body mass: results of an updated data pooling across 18 samples - Carl, Johannes; Zheng, Miaobing; Popp, Johanna; Eckert, Katharina; Geidl, Wolfgang; Blaschke, Simon; Schmid, Julia; Grüne, Eva; Oppermann, Leonard; Liphardt, Anna-Maria; Morf, Harriet; Weißenfels, Anja; et al. (Obesity, 2024)
Objective: Although previous studies have illuminated associations between body mass and physical activity (PA), there have been scant insights regarding the physical, cognitive, and motivational determinants of PA in relationship to body mass. This study aimed to model courses of competencies for health-enhancing PA across the spectrum of BMI. Methods: We used cross-sectional data of 3670 individuals (mean [SD]: BMI, 25.54 [5.71] kg/m2; age, 46.11 [14.96] years) from a large data pooling with 18 primary samples employing the PA-related health competence (PAHCO) instrument. ANCOVA determined differences in 10 PAHCO indicators by BMI categories (underweight, normal weight, overweight, and obesity). Covariate-adjusted multilevel models described the nonlinear courses of the PAHCO indicators across the BMI spectrum. Results: The levels of all 10 PAHCO indicators differed significantly among the BMI categories (F ≥ 14.8; p < 0.001). All competencies for health-enhancing PA could be best described by cubic functions having their maximum around normal weight while regressing with underweight and with increasing grades of obesity (0.02 ≤ (Formula presented.) ≤ 0.31). Conclusions: This study adds to associations between BMI and PA levels by specifying individuals' multidimensional requirements for health-enhancing PA. The present findings call for an integration of physical, motivational, and cognitive factors in practices of PA promotion and sustainable obesity treatment.
CRIS-Team Scopus Importer:2024-10-04

Co-producing a physical activity referral scheme for the German healthcare system: A qualitative analysis of stakeholder experiences - Klamroth, Sarah; Mino, Eriselda; Naber, Inga; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (15th conference of HEPA Europe "Optimising health enhancing physical activity: the importance of inclusion", 2024)

Coproducing a physical activity referral scheme in Germany: A qualitative analysis of stakeholder experiences - Klamroth, Sarah; Mino, Eriselda; Naber, Inga; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (BMJ Open, 2024)
Objectives This study evaluated stakeholders' experiences of participating in a coproduction process to develop a physical activity referral scheme (PARS) in the German healthcare system. The focus was on examining facilitators and challenges, along with gathering insights on potential modifications to the joint development process, all from the viewpoint of stakeholders. Design This qualitative study employed one-to-one semi-structured interviews, and the findings were analysed using summarising qualitative content analysis. Setting The study focused on the German healthcare system. Participants Seven stakeholders from the coproduction process were purposefully selected for interviews using maximum variation sampling. The interviewees represented different sectors (physician associations, physical activity professionals' associations, health insurance companies and patient organisations), various positions within their organisations, and different levels of attendance during the coproduction process. Results In almost all interviews, the following factors were highlighted as facilitators of the development process: coproduction approach, process of coproduction, multi-sector stakeholder group, possibility of active participation, coordinating role of researchers, communication, atmosphere and interaction. In contrast, differences in roles and hierarchy, merging of different perspectives, clarification of intervention costs, and competition and conflicting interests were pointed out as challenges. Only a few suggestions regarding adaptations in terms of group composition and cooperation among stakeholders were mentioned. Conclusions Stakeholder experiences with the joint development process were predominantly positive, indicating that coproduction is a beneficial approach for the development of PARS intended for integration into healthcare systems. The effective management of power differences among stakeholders is intricately tied to the coproduction method; therefore, it should be selected carefully. The research team plays a pivotal role in coordinating and negotiating the process, and the team should be equipped with a diverse set of skills and knowledge, particularly to understand the intricacies of the healthcare system where the PARS is intended for implementation. Trial registration number NCT04947787.
CRIS-Team Scopus Importer:2024-05-31
Keywords: health services; patient participation; primary health care; qualitative research

Co-production of a physical activity referral scheme in the German healthcare system - Geidl, Wolfgang; Klamroth, Sarah; Mino, Eriselda; Weißenfels, Anja; Naber, Inga; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (International Society for Physical Activity and Health (ISPAH) Congress 2024, 2024)
Background: Physical activity referral schemes (PARS) have the potential to promote physical activity (PA) among the mostly inactive primary care population with non-communicable diseases (NCD). No PARS has yet been structurally implemented in the German primary care system. Purpose: The research project BewegtVersorgt aims to develop, implement and evaluate a PARS to promote PA for persons with NCD within the German healthcare system. Methods: The PARS was developed using a co-production approach which integrated twelve organizations from different sectors (health insurances, physicians, exercise professionals, patients’ representatives). Three co-production meetings were applied where individual ideas and current evidence were combined, and different PARS models were elaborated. Finally, all stakeholders agreed on one PARS for implementation as a regional model project and seven stakeholders were purposefully selected for interviews to evaluate the co-production process. Results: The co-produced PARS starts with the primary care physician who offers PA advice and afterward refers patients to an exercise professional. The exercise professional delivers the remaining components of the intervention: initial assessment, six 1-hour individual PA counselling sessions, final assessment. From stakeholder perspective, the following factors were highlighted as facilitators of the development process: co-production approach, process of co-production, multi-sector stakeholder group, possibility of active participation, coordinating role of researchers, communication, atmosphere and interaction. In contrast, differences in roles and hierarchy, merging of different perspectives, clarification of intervention costs, and competition and conflicting interests were pointed out as challenges. Conclusions: By using the co-production approach, it was possible to develop a new PARS and implement it as regional model project in routine practice. Practical implications: Co-production is a beneficial approach for the development of PARS intended for integration into healthcare systems. Support/Funding Source: The study is funded by the Federal Ministry of Health based on a resolution of the German ‘Bundestag’ by the federal governmen

Co-production of a physical activity referral scheme in the German health care system - Mino, Eriselda; Klamroth, Sarah; Weißenfels, Anja; Naber, Inga; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (HEPA Europe, 2023)
Purpose Physical activity referral schemes (PARS) have the potential to promote physical activity (PA) among the mostly inactive primary care population with non-communicable diseases (NCD). Despite significant expansion throughout Europe, a national scheme has not yet been established in Germany. Thus, the ongoing research project BewegtVersorgt aims to develop, implement, and evaluate a PARS to promote PA for persons with NCD within the German healthcare system. Methods The PARS was developed using a co-production approach which integrated twelve organizations from different sectors within the healthcare system (health insurances, physicians, exercise professionals, patients’ representatives) and was guided by the research team. Initially, stakeholders’ ideas of a PARS were collected in individual interviews. These were followed by three co-production meetings where individual ideas and current evidence were combined, and different PARS models for the German setting were elaborated. Finally, all stakeholders agreed on one PARS for implementation as a regional model project. Results The co-produced PARS starts with the primary care physician, as the gatekeeper in the German healthcare system, who offers 10 min PA advice to the patients who would benefit from PA participation. Afterward, the patients are referred to an exercise professional through a referral form. The exercise professional delivers the remaining central components of the intervention - initial assessment, six 1-hour individual PA counseling sessions spread throughout 12 weeks, final assessment, a progress report to the general practitioner, and one follow-up visit at six months. The intervention uses a patient-centered approach and motivational interviewing. The end goal is an adaptation of an active lifestyle and transfer to local physical activity opportunities. Conclusions By using a co-production approach, the expertise of different stakeholders within the healthcare system as well as scientific findings could be integrated into the development process of the PARS. To which extent this participatory approach leads to greater acceptance of the new healthcare service among the implementing actors and positively influences their cooperation within the PARS will be evaluated during the implementation phase. Support/Funding Source The study is funded by the Federal Ministry of Health based on a resolution of the German ‘Bundestag’ by the federal government.

Coproduction to improve preventive health services—experiences from Germany - Abu-Omar, Karim; Weißenfels, Anja; Mino, Eriselda; Naber, Inga; Klamroth, Sarah; Geidl, Wolfgang; Pfeifer, Klaus (Health promotion international, 2021)
Due to the beneficial impact of regular physical activity (PA) on non-communicable diseases, the number of countries integrating exercise referral schemes (ERSs) into their healthcare systems is growing. Owing to the limitations of existing PA promotion concepts in Germany’s healthcare system, efforts are currently being made towards developing a nationwide referral pathway. A research group at the Friedrich-Alexander-University Erlangen-Nürnberg is coordinating these efforts within a project funded by the Federal Ministry of Health. The aim is to develop, implement and evaluate a regional-level ERS that has the potential to be scaled up across Germany in the event of its demonstrated effectiveness. The project is based on an adapted Cooperative Planning approach requiring interaction between the academic sector and different actors of the healthcare sector. The present commentary reflects on challenges faced in the early stages of the co-production process. Besides the development of an adequate co-production methodology, it critically discusses stakeholder participation, knowledge gaps and actors’ willingness to take responsibility. In addition, although patients are represented by dedicated organizations, their perspective cannot be adequately captured using a co-production approach. Despite the joint development of an ERS, there remain important questions regarding the appropriateness of the co-production approach in a healthcare setting.
Keywords: physical activity promotion; exercise referral scheme; co-production process; non-communicable diseases; primary healthcare

Corrigendum: Position statement and updated international guideline for safe and effective whole-body electromyostimulation training-the need for common sense in WB-EMS application (Frontiers in Physiology, (2023), 14, (1174103), 10.3389/fphys.2023.1174103) - Kemmler, Wolfgang; Fröhlich, Michael; Ludwig, Oliver; Eifler, Christoph; von Stengel, Simon; Willert, Sebastian; Teschler, Marc; Weißenfels, Anja; Kleinöder, Heinz; Micke, Florian; Wirtz, Nicolas; Zinner, Christoph; et al. (Frontiers in Physiology, 2023)
In the published article, the citation of Author Jaskanwal Deep Singh Sara was incorrectly written as “Singh Sara JD” instead of “Sara JDS.” The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2023-06-02
Keywords: electrical muscle stimulation; international consensus; recommendations; safety; whole-body electromyostimulation

Development, implementation, evaluation and scaling-up of physical activity referral schemes in Germany: protocol for a study using a co-production approach - Weißenfels, Anja; Geidl, Wolfgang; Mino, Eriselda; Naber, Inga; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (BMJ Open, 2021)
Introduction Physical activity referral schemes (PARSs) are recommended to promote physical activity (PA) among adults at risk of developing or with established non-communicable diseases (NCDs). In Germany, this kind of referral schemes has not yet been implemented systematically and nationwide. In this study protocol, we present the methodological design of a co-production research study aimed at establishing a PARS for adults with NCDs in German primary healthcare. Methods and analysis We will employ a co-production approach consistently throughout the four project phases: (1) development of the PARS; (2) preparation period; (3) implementation and evaluation; (4) development of a strategic plan for scaling up the PARS to the national level as part of standard care. The first phase will additionally include a status quo analysis of the existing physical activity pathways nationwide as well as an overview of international PARS models. A pragmatic trial design will be used for evaluating the developed PARS. The co-production approach will involve relevant actors in the German healthcare system, namely, healthcare service providers (eg, physicians, exercise professionals), health insurance providers, exercise providers, patients’ representatives, experts in the development and implementation of educational concepts, and scientists from the fields of sports science and public health. Ethics and dissemination The project has been reviewed and approved by the ethics committee of the Friedrich-Alexander-University Erlangen-Nürnberg (ethics approval number: 331_20 B). Through cooperation agreements, the stakeholders involved gave their consent to participate and were informed about the study in detail. The results of this study will be disseminated by international conference presentations and peer-reviewed publications, and if possible, a manual for the use of the PARS will be provided.

Drop-out-Analysen in einer pragmatischen Implementierungsstudie zur Bewegungsförderung im deutschen Gesundheitssystem - Mino, Eriselda; Klamroth, Sarah; Weißenfels, Anja; Naber, Inga; Geidl, Wolfgang; Gelius, Peter; Pfeifer, Klaus (Abstractband, 2024)
Einleitung Drop-out-Analysen in Interventionsstudien spielen im Zusammenhang mit der Förderung der Motivation für körperliche Aktivität bei Menschen mit chronischen nichtübertragbaren Erkrankungen (NCD) eine wichtige Rolle. Im Projekt BewegtVersorgt wurde in einer pragmatischen Implementierungsstudie (02/2022-12/2023) eine neue Bewegungsversorgungskette (PARS: ärztliche Kurzberatung und individuelle Bewegungsförderung durch Therapeut*innen) mit einer alleinigen strukturierten ärztlichen Kurzberatung (PAA) verglichen. Das Ziel der vorliegenden Studie ist die Analyse der Drop-out Faktoren für beide Interventionsformen. Methode Die Drop-out-Analyse wurde mittels binärer logistischer Regressionen durchgeführt (SPSS 29.0). Die Teilnehmercharakteristika zu Studienbeginn wurden dabei als unabhängige Prädiktoren integriert. Zusätzlich wurden die Teilnehmenden telefonisch mittels strukturiertem Gesprächsleitfaden zu den Gründen des Studienabbruchs befragt. Ergebnisse Von insgesamt 168 Studienteilnehmenden (PARS n=109; PAA n=59) haben 54,1 % (PARS) und 47,5 % (PAA) die Intervention abgebrochen, ohne signifikanten Unterschied zwischen den Gruppen. In der PARS-Gruppe erhöhte das Vorliegen einer koronaren Herzkrankheit die Drop-out-Wahrscheinlichkeit um den Faktor 4,3 (95%KI: 1,2-15,6; R2: 0,127). In der PAA-Gruppe war die Drop-out-Rate bei Männern 4,1-mal höher als bei Frauen (95%KI: 1,3-12,3; R2: 0,135), ein Trend der sich auch bei PARS abzeichnete (p=0,058). Bei der telefonischen Befragung der Drop-out-Gründe wurden bei PARS gesundheitliche Probleme (24%) und bei PAA mangelnde Fragebogen-Compliance (36%) sowie andere Prioritäten (PARS 17%; PAA 14%) am häufigsten berichtet. Diskussion Die vorliegenden Ergebnisse liefern relevante Erkenntnisse für die Bewegungsförderung von Personen mit NCD in der Gesundheitsversorgung. Der Einfluss der Corona-Pandemie auf diese Implementierungsstudie ist vor dem Hintergrund der Überlastung des Gesundheitssystems, eingeschränkter regionaler Bewegungsangebote und gesundheitlicher Einschränkungen der Teilnehmenden besonders zu berücksichtige
Keywords: Bewegungsförderung; Gesundheitsversorgung; Menschen mit chronischen nichtübertragbaren Erkrankungen; Drop-out Faktoren

Effectiveness and implementation success of a co-produced physical activity referral scheme in Germany: study protocol of a pragmatic cluster randomised trial - Weißenfels, Anja; Klamroth, Sarah; Carl, Johannes; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (BMC Public Health, 2022)
Background While effective physical activity referral schemes (PARSs) and related structures for promoting physical activity (PA) already exist in several countries, in Germany, PARSs have not yet been implemented systematically and nationwide. Through a co-production approach with relevant actors in the German healthcare system, a PARS was developed, and an implementation plan was created (e.g. financing). This study protocol aims to evaluate the developed PARS for people with non-communicable diseases (NCDs) in Germany regarding its potential effectiveness and implementation success. Methods To evaluate the effectiveness and implementation success of the PARS, we will apply a pragmatic cluster-randomised controlled trial (cRCT) in Hybrid II design by comparing two intervention groups (PARS vs PA advice [PAA]). The trial will take place in the Nürnberg metropolitan region, with 24 physician practices recruiting 567 people with NCDs. Both groups will receive brief PA advice from a physician to initially increase the participants’ motivation to change their activity level. Subsequently, the PARS group will be given individualised support from an exercise professional to increase their PA levels and be transferred to local exercise opportunities. In contrast, participants in the PAA group will receive only the brief PA advice as well as information and an overview of regional PA offerings to become more active at their own initiative. After 12 and 24 weeks, changes in moderate to vigorous PA and in physical activity-related health competence (movement competence, control competence, self-regulation competence) will be measured as primary outcomes. Secondary outcomes will include changes in quality of life. To measure implementation success, we refer to the RE-AIM framework and draw on patient documentation, interviews, focus groups and surveys of the participating actors (physicians, exercise professionals). Discussion Through a between-group comparison, we will investigate whether additional individual support by an exercise professional compared to brief PA advice alone leads to higher PA levels in people with NCDs. The acceptance and feasibility of both interventions in routine care in the German healthcare system will also be evaluate
CRIS-Team WoS Importer:2022-08-26

Effect of deep oscillation as a recovery method after fatiguing soccer training: A randomized cross-over study - von Stengel, Simon; Teschler, Marc; Weißenfels, Anja; Willert, Sebastian; Kemmler, Wolfgang (Journal of Exercise Science & Fitness, 2018)
Background/Objective: In soccer the recovery time between matches is often not long enough for complete restoration. Insufficient recovery can result in reduced performance and a higher risk of injuries. The purpose of this study was to evaluate the potential of Deep Oscillation (DO) as a recovery method. Methods: In a randomized crossover study including 8 male soccer players (22 ± 3.3 years) the following parameters were evaluated directly before and 48 h after a fatiguing soccer-specific exercise: Maximum isokinetic strength of the leg and hip extensors and flexors (Con-Trex® Leg Press, Physiomed, Germany), rating of perceived exertion (RPE) during isokinetic testing (Borg scale 6-20), creatine kinase (CK) serum levels and Delayed Onset Muscle Soreness (DOMS; visual analogue scale 1-10). By random allocation, half of the group performed a DO self-treatment twice daily (4 applications of 15min each), whilst the other half received no intervention. 4 weeks later a cross-over was conducted. Two-way repeated measures analysis of variance was used to compare treatment versus control. Results: A significant treatment effect was observed for maximum leg flexion strength (p = 0.03; DO: 125 ± 206 N vs. CG: -115 ± 194; p = 0.03) and for RPE (DO: -0.13 ± 0.64; vs. CG: +1.13 ± 1.36; p = 0.03). There was a trend to better recovery for maximum leg extension strength (DO: -31 ± 165 N vs. CG: -138 ± 212; p = 0.028), CK values (DO: 72 ± 331 U/ml vs. CG: 535 ± 797 U/ml; p = 0.15) and DOMS (DO: 3.4 ± 1.5 vs. CG: 4.1 ± 2.6; p = 0.49). Conclusion: In the present study we found significant effects of DO on maximum leg flexion strength and perceived rate of exertion. Other variables showed a consistent trend in favour of DO compared with the control without significance. DO seems to be a promising method to accelerate the time-course of peripheral recovery of muscle which should be addressed in larger studies in future. Trial registration: ClinicalTrials.gov; NCT03411278, 18.01.2018 (during the study).
EVALuna2:214333

Effects of whole-body electromyostimulation on chronic nonspecific low back pain in adults: a randomized controlled study - Weißenfels, Anja; Teschler, Marc; Willert, Sebastian; Hettchen, Michael; Froehlich, Michael; Kleinoeder, Heinz; Kohl, Matthias; von Stengel, Simon; Kemmler, Wolfgang (Journal of Pain Research, 2018)
Purpose: Low back pain (LBP) is one of the most frequent chronic conditions worldwide. Data from a recent meta-analysis indicated that whole-body electromyostimulation (WB-EMS), a time-effective, joint-friendly, and highly individualized training technology, demonstrated promising effects on LBP; however, methodologic limitations prevent definitive evidence for this result. Thus, the aim of this study was to conduct a randomized controlled WB-EMS trial to determine the corresponding effect on chronic, nonspecific LBP in people with chronic LBP. Patients and methods: Thirty LBP patients, 40-70 years old, were randomly assigned into two groups (WB-EMS: 15; control [CG]: 15). While the nonactive CG maintained their lifestyle, the WB-EMS group completed a 12-week WB-EMS protocol (1×20 min/week) with slight movements, specifically dedicated to LBP. Pain intensity and frequency were determined by a 4-week pain diary before and during the last 4 weeks of intervention. Primary study endpoint was average pain intensity at the lumbar spine. Results: At baseline, no group differences apart from nonregular exercise were observed. Mean intensity of LBP decreased significantly in the WB-EMS group (P=0.002) and remained unchanged in the CG (P=0.730), with a significant difference between both groups (P=0.027). Maximum isometric trunk extensors improved significantly in the WB-EMS group (P=0.005), while no significant difference was seen in the CG (P=0.683). In contrast to the significant difference between WB-EMS group and CG for the latter parameter (P=0.038), no intergroup difference was determined for maximum isometric trunk flexors (P=0.091). The WB-EMS group showed a significant increase of this parameter (P=0.003), while no significant change was determined in the CG (P=0.563). Conclusion: WB-EMS is a time-effective training method for reducing chronic nonspecific LBP and increasing maximum trunk strength in people with such complaints. After this promising comparison with a nonactive CG, research needs to be extended to include comparisons with active groups (WB-Vibration, conventional back strengthening).
EVALuna2:214339

Effects of Whole-Body Electromyostimulation on Low Back Pain in People with Chronic Unspecific Dorsal Pain: A Meta-Analysis of Individual Patient Data from Randomized Controlled WB-EMS Trials - Kemmler, Wolfgang; Weißenfels, Anja; Bebenek, Michael; Froehlich, Michael; Kleinoeder, Heinz; Kohl, Matthias; von Stengel, Simon (Evidence-based complementary and alternative medicine, 2017)
In order to evaluate the favorable effect of whole-body electromyostimulation (WB-EMS) on low back pain (LBP), an aspect which is frequently claimed by commercial providers, we performed a meta-analysis of individual patient data. The analysis is based on five of our recently conducted randomized controlled WB-EMS trials with adults 60 years+, all of which applied similar WB-EMS protocols (1.5 sessions/week, bipolar current, 16-25 min/session, 85 Hz, 350 μs, and 4-6 s impulse/4 s impulse-break) and used the same pain questionnaire. From these underlying trials, we included only subjects with frequent-chronic LBP in the present meta-analysis. Study endpoints were pain intensity and frequency at the lumbar spine. In summary, 23 participants of the underlying WB-EMS and 22 subjects of the control groups (CG) were pooled in a joint WB-EMS and CG. At baseline, no group differences with respect to LBP intensity and frequency were observed. Pain intensity improved significantly in the WB-EMS (p< .001) and was maintained (p= .997) in the CG. LBP frequency decreased significantly in the WB-EMS (p< .001) and improved nonsignificantly in the CG (p= .057). Group differences for both LBP parameters were significant (p≤ .035). We concluded that WB-EMS appears to be an effective training tool for reducing LBP; however, RCTs should further address this issue with more specified study protocols.
EVALuna2:33274

Effects of Whole-Body Electromyostimulation on the Energy-Restriction-Induced Reduction of Muscle Mass During Intended Weight Loss - Willert, Sebastian; Weißenfels, Anja; Kohl, Matthias; von Stengel, Simon; Froehlich, Michael; Kleinoeder, Heinz; Schöne, Daniel; Teschler, Marc; Kemmler, Wolfgang (Frontiers in Physiology, 2019)
Purpose: Overweight and obesity are an increasing problem worldwide. However, most studies that focus on weight reduction by energy restriction and/or aerobic exercise reported considerable loss of muscle mass as well. Increased protein intake and/or resistance exercise might inhibit this detrimental effect during a negative energy balance. Whole-body electromyostimulation (WB-EMS), a time effective, joint-friendly, and highly customizable training technology, showed similar hypertrophic effects compared with high-intensity resistance training. The aim of this study is to evaluate the effect of WB-EMS on body composition during negative energy balance with maintained/increased protein intake in overweight premenopausal women.
CRIS-Team WoS Importer:2019-08-23

Effects of Whole-Body Electromyostimulation versus High-Intensity Resistance Exercise on Body Composition and Strength: A Randomized Controlled Study - Kemmler, Wolfgang; Teschler, Marc; Weißenfels, Anja; Bebenek, Michael; Froehlich, Michael; Kohl, Matthias; von Stengel, Simon (Evidence-based complementary and alternative medicine, 2016)
High-intensity (resistance) exercise (HIT) and whole-body electromyostimulation (WB-EMS) are both approaches to realize time-efficient favorable changes of body composition and strength. The purpose of this study was to determine the effectiveness of WB-EMS compared with the gold standard reference HIT, for improving body composition and muscle strength in middle-aged men. Forty-eight healthy untrained men, 30-50 years old, were randomly allocated to either HIT (2 sessions/week) or a WB-EMS group (3 sessions/2 weeks) that exercised for 16 weeks. HIT was applied as "single-set-to-failure protocol," while WB-EMS was conducted with intermittent stimulation (6 s WB-EMS, 4 s rest; 85 Hz, 350 ms) over 20 minutes. The main outcome parameters were lean body mass (LBM) as determined via dual-energy X-ray absorptiometry and maximum dynamic leg-extensor strength (isokinetic leg-press). LBM changes of both groups (HIT 1.25 ± 1.44% versus WB-EMS 0.93 ± 1.15%) were significant (p = .001); however, no significant group differences were detected (p = .395). Leg-extensor strength also increased in both groups (HIT 12.7 ± 14.7%, p = .002, versus WB-EMS 7.3 ± 10.3%, p = .012) with no significant (p = .215) between-group difference. Corresponding changes were also determined for body fat and back-extensor strength. Conclusion. In summary, WB-EMS can be considered as a time-efficient but pricy option to HIT-resistance exercise for people aiming at the improvement of general strength and body composition.
EVALuna2:33288

Efficacy and Safety of Low Frequency Whole-Body Electromyostimulation (WB-EMS) to Improve Health-Related Outcomes in Non-athletic Adults. A Systematic Review - Kemmler, Wolfgang; Weißenfels, Anja; Willert, Sebastian; Shojaa, Mahdieh; von Stengel, Simon; Filipovic, Andre; Kleinoeder, Heinz; Berger, Joshua; Froehlich, Michael (Frontiers in Physiology, 2018)
Exercise positively affects most risk factors, diseases and disabling conditions of middle to advanced age, however the majority of middle-aged to older people fall short of the exercise doses recommended for positively affecting cardio-metabolic, musculoskeletal and neurophysiological fitness or disabling conditions. Whole-Body Electromyostimulation (WB-EMS) may be a promising exercise technology for people unable or unmotivated to exercise conventionally. However, until recently there has been a dearth of evidence with respect to WB-EMS-induced effects on health-related outcomes. The aim of this systematic review is to summarize the effects, limitations and risks of WB-EMS as a preventive or therapeutic tool for non-athletic adults. Electronic searches in PubMed, Scopus, Web of Science, PsycINFO, Cochrane and Eric were run to identify randomized controlled trials, non-randomized controlled trials, meta-analyses of individual patient data and peer reviewed scientific theses that examined (1) WB-EMS-induced changes of musculoskeletal risk factors and diseases (2) WB-EMS-induced changes of functional capacity and physical fitness (3) WB-EMS-induced changes of cardio-metabolic risk factors and diseases (4) Risk factors of WB-EMS application and adverse effects during WB-EMS interventions. Two researchers independently reviewed articles for eligibility and methodological quality. Twenty-three eligible research articles generated by fourteen research projects were finally included. In summary, thirteen projects were WB-EMS trials and one study was a meta-analysis of individual patient data. WB-EMS significantly improves muscle mass and function while reducing fat mass and low back pain. Although there is some evidence of a positive effect of WB-EMS on cardio-metabolic risk factors, this aspect requires further detailed study. Properly applied and supervised, WB-EMS appears to be a safe training technology. In summary, WB-EMS represents a safe and reasonable option for cohorts unable or unwilling to join conventional exercise programs. However, much like all other types of exercise, WB-EMS does not affect every aspect of physical performance and health.
EVALuna2:214336

Erfahrungen mit der Koproduktion einer Bewegungsversorgungskette: Eine qualitative Auswertung von Stakeholder-Interviews - Klamroth, Sarah; Mino, Eriselda; Naber, Inga; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Schriften der Deutschen vereinigung für Sportwissenschaft, 2023)

Etablierung von Versorgungsketten zur Bewegungsförderung für Menschen mit nichtübertragbaren Erkrankungen – ein partizipativer Ansatz im Projekt BewegtVersorgt - Naber, Inga; Weißenfels, Anja; Klamroth, Sarah; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (19. Deutscher Kongress für Versorgungsforschung, 2020)
Hintergrund und Stand internationaler Forschung: Bewegungsversorgungsketten (BVK) sind in vielen Ländern (z.B. Neuseeland) bereits fest in die Routinepraxis der Gesundheitssysteme eingebettet und zeigen nachhaltige Steigerungen körperlicher Aktivität bei Menschen mit nichtübertragbaren Erkrankungen (NCD) [1]. Zwar befürworten auch nationale Empfehlungen eine ärztlich initiierte Bewegungsversorgung [2], die vorhandenen BVK zielen bislang vornehmlich auf die Verbesserung von Körperfunktionen, weniger auf Bewegungsförderung ab. Fragestellung und Zielsetzung: Vor dem Hintergrund vorliegender Evidenz stellt sich für Deutschland die Frage, wie verhaltensbezogene Bewegungsförderung in BVK integrieren werden kann. Das Ziel des Projekts BewegtVersorgt (im Förderschwerpunkt Bewegung und Bewegungsförderung des BMG) ist es, über einen partizipativen Ansatz BVK für Menschen mit NCD zu entwickeln, auf regionaler Ebene zu erproben und nach positiver Evaluation einen Transfer in die nationale Regelversorgung vorzubereiten. Methode: Zur Erreichung des Projektziels in Phase 1 wurde, ebenso wie im gesamten Projektverlauf, ein Co-Creation Ansatz mit Akteuren des Gesundheitssystems (Kostenträger, Ärzte, Patientenvertretung, Leistungserbringer/Bewegungsanbieter) verfolgt. Der Entwicklungsprozess beinhaltete 1. qualitative Interviews mit den Projektpartnern über Hindernisse/Förderfaktoren und ihre eigene Rolle in der Umsetzung von BVK, 2. systematische Literaturrecherche zur Identifizierung von Kernelementen sowie 3.drei Planungstreffen zur partizipativen Entwicklung möglicher BVK unter Einbeziehung der eruierten Kernelemente. Ergebnisse: In der ersten Projektphase wurden sieben int. Kernelemente als Teil der BVK identifiziert: Assessment, Beratung, schriftliche und verbindliche Verordnung, individualisierte Bewegungsempfehlungen, Verhaltensänderungstechniken, unterstützende Person, Follow-up. Gute Kommunikation zwischen den Akteuren sowie konstruktives Feedback wurden als Förderfaktoren identifiziert. Entsprechend wurden in den partizipativen Planungstreffen Schwimmbahnmodelle für potenzielle BVK für Deutschland entwickelt. Diskussion: Die Nutzung des Co-Creation-Ansatzes ermöglichte die konsensuale Einigung auf Varianten einer BVK. Der fortlaufende partizipative Prozess sowie das Überwinden von möglichen Barrieren werden eine kontinuierliche Anpassung der BVK erfordern. Die Wirksamkeit sowie die Kosten-Effektivität der BVK müssen im nächsten Schritt pilotartig erprobt und evaluiert werden. Praktische Implikationen: Das partizipative Vorgehen unter Beteiligung relevanter Akteure erhöht die Chancen der Akzeptanz und nachhaltigen Implementierung der BVK. Basierend auf den Evaluationsergebnissen der Umsetzungsphase wird ein Disseminierungskonzept zum Transfer in die bundesweite Regelversorgung erstellt.

Förderung von bewegungsbezogener Gesundheitskompetenz in ärztlich verordneten Bewegungsinterventionen – Aufbau des Interventionskonzeptes im Forschungsprojekt BewegtVersorgt. - Naber, Inga; Klamroth, Sarah; Weißenfels, Anja; Geidl, Wolfgang; Streber, René; Mino, Eriselda; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Bewegungstherapie und Gesundheitssport, 2022)
Die ärztlich-initiierte Verordnung von Bewegung kann als effektive Methode zur Bewegungsförderung von Menschen mit nichtübertragbaren Erkrankungen (non-communicable diseases – NCD) eingesetzt werden. Die Förderung der bewegungsbezogenen Gesundheitskompetenz (BGK) im Rahmen der verordneten Bewegung beeinfl usst die Gesundheitswirkungen, den Bewältigungsprozess sowie das Bewegungsverhalten positiv. In diesem Artikel wird ein BGK-basiertes Interventionskonzept zur ärztlich-initiierten Bewegungsförderung vorgestellt, welches im Projekt BewegtVersorgt entwickelt wurde. Das Forschungsprojekt BewegtVersorgt hat das Ziel, in Deutschland eine solche ärztlich-initiierte Bewegungsversorgungskette zur systematischen Bewegungsförderung für Menschen mit NCD zu entwickeln, zu erproben und zu evaluieren. Im Rahmen des Projekts haben sich zwölf Organisationen aus unterschiedlichen Bereichen des Gesundheitssystems (Ärzteschaft, Kostenträger, Bewegungsanbieter, Vertretung der Betroff enen) an der Entwicklung einer Bewegungsversorgungskette beteiligt. Diese Versorgungskette wird in Form eines Modellprojektes nach §§ 63 Abs. 2, 64 SGB V gemeinsam mit ärztlichem Fachpersonal, Bewegungsfachpersonal und Bewegungsanbietern in der Routineversorgung für ein Jahr erprobt. Die Kernkomponente der Bewegungsversorgungskette stellt die individuelle Bewegungsförderung (IBF) dar, welche basierend auf dem Modell der BGK entwickelt wurde und von speziell geschultem Bewegungsfachpersonal durchgeführt wird. Das Konzept ist modular aufgebaut, integriert spezifi sche Methoden sowie Arbeitsmaterialien und umfasst eine 1:1 Betreuung über einen Zeitraum von 24 Wochen (6 Einheiten à 60 Minuten und drei Assessments). Nach der Erprobung werden der Implementierungserfolg in der Routineversorgung sowie die Wirksamkeit der Versorgungskette im Hinblick auf die Steigerung des körperlichen Aktivitätslevels und der BGK evaluiert. Sollte sich das neue Versorgungskonzept als wirksam erweisen, ist für die letzte Projektphase die Entwicklung eines Transfer- und Skalierungskonzepts zur nachhaltigen Verankerung in der Gesundheitsversorgung geplant.<br
Keywords: Körperliche Aktivität; ärztlich-initiierte Bewegungsförderung; Versorgungsstrukturen; individuelle Bewegungsförderung; bewegungsbezogene Gesundheitskompetenz

Ganzkörper Elektromyostimulation versus HIT-Krafttraining – Einfluss auf Körperzusammensetzung und Muskelkraft - Kemmler, Wolfgang; Teschler, Marc; Weißenfels, Anja; Froehlich, M.; Kohl, M.; von Stengel, Simon (Deutsche Zeitschrift für Sportmedizin, 2015)
Purpose: High Intensity (resistance exercise) Training (HIT) and Whole-Body Electromyostimulation (WB-EMS) may be the most promising approaches to generate favorable changes of body composition and strength with optimum time-efficiency. In this study, we compared the effect of WB-EMS on body composition and muscle strength with the “golden standard” HIT over 16 weeks. Methods: 30-50 year-old men (n=48) were randomly allocated to a HIT (n=24) with 2 sessions/week of a “single-set-to-failure- protocol” or a WB-EMS-group that exercised 3 sessions in two weeks, using intermittent stimulation (6 sec - 4 sec rest; 85 Hz, 350 ms) over 20 min. An Intention to treat analysis was calculated with Lean Body Mass (LBM) defined as primary endpoint, and appendicular skeletal muscle mass (ASMM), maximum dynamic leg-extensor and isometric back-extensor strength as secondary endpoints. ››Results: Net exercise time/session was 30.3 ±2.3 for HIT vs. 20 ±0 min for WB-EMS (p<.001). LBM (HIT: 1.24 ±1.40% vs. WB-EMS: 0.91 ±1.12%) and ASMM (1.92 ±1.51% vs. WB-EMS: 1.52 ±1.48%) significantly increased (p≤.003), with no significant group differences (LBM: p=.406 and ASMM: p=.341). In parallel, changes of maximum dynamic leg strength (HIT: 13.5 ±13.9%, p=.001 vs. WBEMS: 8.0 ±10.2%, p=.008) and maximum isometric back strength (10.4 ±9.0%, p<.001 vs. 11.7 ±9.9%; p<.001) were comparable (p=.332 and p=.609) between groups. Discussion: In conclusion, compared to HIT, WB-EMS can be considered as an even more time-efficient but pricey option for subjects who aim to improve their body composition and general strength.
Created from Fastlane, Scopus look-up
Keywords: Electrostimulation; HIT; Muscle mass; Muscle strength; Muscle training

Implementation of a physical activity referral scheme in the German healthcare system: A qualitative analysis of implementation success - Klamroth, Sarah; Lorenz, Eva; Naber, Inga; Mino, Eriselda; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (15th conference of HEPA Europe "Optimising health enhancing physical activity: the importance of inclusion", 2024)

Implementation success of a physical activity referral scheme (PARS) in the German healthcare system - Klamroth, Sarah; Lorenz, Eva; Naber, Inga; Mino, Eriselda; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (10th ISPAH Congress "Accelerating policy and practice to ensure physical activity for all", 2024)

Implementierung bewegungsbezogener Interventionen in der Routine-versorgung: Erfahrungen aus dem Forschungsprojekt BewegtVersorgt - Klamroth, Sarah; Weißenfels, Anja; Mino, Eriselda; Naber, Inga; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Jahrestagung der dvs-Kommission Gesundheit, 2022)

Implementierungserfolg einer Bewegungsversorgungskette im deutschen Gesundheitssystem: Eine qualitative Analyse aus der Perspektive von Ärzt*innen und Bewegungstherapeut*innen - Klamroth, Sarah; Lorenz, Eva; Naber, Inga; Mino, Eriselda; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Jahrestagung der dvs-Kommission Gesundheit "Sport, Bewegung und Ernährung - unzertrennlich für einen gesunden Lebensstil?", 2024)

Koproduktion und Implementierung einer Bewegungsversorgungskette für Menschen mit nichtübertragbaren Erkrankungen: Projekt BewegtVersorgt - Pfeifer, Klaus; Weißenfels, Anja; Klamroth, Sarah; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim (22. Deutscher Kongress für Versorgungsforschung, 2023)

Koproduktion und Implementierung von Ärztlich-initiierter Bewegungsförderung für Menschen mit nichtübertragbaren Erkrankungen - Weißenfels, Anja; Klamroth, Sarah; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Sports, Medicine and Health Summit 2023, 2023)

Methods for segmentation of rheumatoid arthritis bone erosions in high-resolution peripheral quantitative computed tomography (HR-pQCT) - Figueiredo, Camille P.; Kleyer, Arnd; Simon, Dominic; Stemmler, Fabian; d'Oliveira, Isabelle; Weißenfels, Anja; Museyko, Oleg; Friedberger, Andreas; Hueber, Axel; Haschka, Judith; Englbrecht, Matthias; Pereira, Rosa M.R.; et al. (Seminars in Arthritis and Rheumatism, 2017)
The comparison between different techniques to quantify the 3-dimensional size of inflammatory bone erosions in rheumatoid arthritis(RA) patients.Anti-cyclic citrullinated peptide antibody(ACPA) positive RA patients received high-resolution peripheral quantitative computed tomography (HR-pQCT) scans of the metacarpophalangeal joints (MCP). Erosions were measured by three different segmentation techniques: (1) manual method with calculation by half-ellipsoid formula, (2) semi-automated modified Evaluation Script for Erosions (mESE), and (3) semi-automated Medical Image Analysis Framework (MIAF) software. Bland & Altman plots were used to describe agreement between methods. Furthermore, shape of erosions was classified as regular or irregular and then compared to the sphericity obtained by MIAF.A total of 76 erosions from 65 RA patients (46 females/19 males), median age 57 years, median disease duration 6.1 years and median disease activity score 28 of 2.8 units were analyzed. While mESE and MIAF showed good agreement in the measurement of erosion size, the manual method with calculation by half-ellipsoid formula underestimated erosions size, particularly with larger erosions. Accurate segmentation is particularly important in larger erosions, which are irregularly shaped. In all three segmentation techniques irregular erosions were larger in size than regular erosions (MIAF: 19.7 vs. 3.4mm(3); mESE: 15.5 vs. 2.3mm(3); manual = 7.2 vs. 1.52mm(3); all p < 0.001). In accordance, sphericity of erosions measured by MIAF significantly decreased with their size (p < 0.001).MIAF and mESE allow segmentation of inflammatory bone erosions in RA patients with excellent inter reader reliability. They allow calculating erosion volume independent of erosion shape and therefore provide an attractive tool to quantify structural damage in individual joints of RA patients.
EVALuna2:13514

P07-04 A systematic review of key interventional elements in international exercise referral schemes - Mino, Eriselda; Hanson, Coral; Geidl, Wolfgang; Naber, Inga; Mchale, Sheona; Klamroth, Sarah; Weißenfels, Anja; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (European Journal of Public Health, Volume 32, Issue Supplement_2, 2022)
Background With the first initiatives dating back to the 1990s, the past two decades have seen a rapid increase in the use of exercise referral schemes (ERS) worldwide. Despite the accumulating evidence on their effectiveness, there are currently no international guidelines available to inform the design of such interventions. The key elements and processes employed vary both within and between countries. This systematic review aims to address this frequently overlooked topic by identifying elements that are predominant in international ERS. Methods Scientific databases (PubMed, Scopus) and grey literature sources were systematically searched. In order to collect the information relevant for understanding and visualizing all ERS models, a broad spectrum of document types was considered eligible for inclusion, i.e. randomized controlled or pragmatic trials, cohort studies, case-control studies, case series, case reports, qualitative studies, economic evaluations, mixed designs, policy documents, and official governmental reports. We extracted data on scheme components, contents, and main actors involved in scheme delivery. Cross-functional flowcharts were employed to facilitate comparison between different ERS designs: Firstly, the collected data were visualized in flowcharts indicating the pathway a patient follows from beginning to end of an individual ERS. Secondly, elements that appeared more frequently across all included ERS were identified. Results Preliminary results identified 18 models of ERS that were eligible for data analysis, including Green Prescription (New Zealand), Hreyfiseðill (Iceland), National Exercise Referral Scheme (Wales). Program designs ranged from short advice by a primary healthcare professional to physical activity prescription and/or further referral to affiliated health professionals. The prevailing actors involved in scheme delivery were physicians, nurses, physiotherapists, training experts, physical activity providers, and coordinators. Seven predominant elements emerged from the comparison between ERS designs: assessment, counselling, individualized physical activity recommendations, written prescription, behavior change techniques, support person, and follow-up. Conclusions To the best of our knowledge, this is the first study that takes a closer look at the design characteristics of ERS across the world. Our preliminary results indicate that there are seven key elements. The contribution of these elements on the effectiveness of ERS needs to be explored in future research.
Keywords: exercise referral scheme; exercise prescription; physical activity on prescription scheme; physical activity promotion; primary health care

P07-12 Stakeholders perspectives on exercise referral schemes in Germany - Naber, Inga; Mino, Eriselda; Klamroth, Sarah; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (2022)
Background There is a growing popularity of exercise referral schemes (ERS) and they are widely implemented in nations such as New Zealand and Sweden. To this point, the German health care system (GHCS) is not utilising a structurally implemented ERS, but a research project is currently conducted to develop and test a German ERS. In the first project phase, the aim was to introduce the topic of ERS to relevant stakeholders of the GHCS and to gather their expert opinions on such a potential ERS. Further, the aim was to familiarise the stakeholders to the project and its collaborative approach in developing and testing an ERS. Methods Semi-structured interviews were conducted with 12 relevant stakeholder of the GHCS. In each case, two researchers conducted the interviews between June to September 2019. Main topics addressed during the interviews were potential target groups for an ERS, their own role within an ERS, PA counselling and dropouts that would be expected. During the interviews, stakeholders were encouraged to sketch their ideas for how to organise an ERS on paper. In the analysis, we digitalised these sketches into flow-chart diagrams. Results The analysis of the interviews showed that the sketches proposed innovative additions and alternative PA promotion strategies within the GHCS. The stakeholders identified barriers within the GHCS such as the rigid costing of treatments and performance measurements. Some reoccurring important core elements for an ERS in Germany were suggested: having a supportive person, implementing PA behaviour impact, utilising existing PA programs and tailoring individual PA counselling. Some stakeholders envisioned an ERS focusing on their perspectives and desired role within the ERS while others outlined ERS that largely excluded them. Conclusions All stakeholders clearly expressed the need for collaboration to develop and test an ERS in Germany. Previous studies have been focused on factors that influence effectiveness, as uptake and adherence. In contrast, these interviews resulted in the identification of concrete barriers and facilitators from the administrative perspective within the GHCS. Different stakeholders show varying degrees of interest in being part of an ERS. This information is highly valuable for the upcoming collaborative process.
Keywords: exercise referral; physical activity promotion; primary healthcare; participatory research approach; physical activity on prescription

Physical activity referral scheme components: a study protocol for systematic review and meta-regression - Mino, Eriselda; Geidl, Wolfgang; Naber, Inga; Weißenfels, Anja; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (BMJ Open, 2021)
Introduction In its attempt to establish effective physical activity promotion methods, research on physical activity referral schemes (PARS) is attracting significant attention. Sometimes known as physical activity on prescription schemes, PARS involve a well-defined procedure whereby a primary healthcare professional introduces a participant to the topic of physical activity and employs prescription or referral forms to connect the participant to physical activity opportunities, such as local fitness offers. The planned systematic review will focus on these referral routes and scheme components and how they are integrated into various PARS models worldwide. We seek to identify the evidence-based core components that play the most important roles in the effectiveness of PARS. Methods and analysis The development and reporting of the protocol follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines. We plan to conduct a systematic main literature search on PubMed, Scopus, Web of Science, CINAHL, HTA, SpringerLink and other databases. We will include studies that report outcomes on physical activity, PARS uptake and adherence rates or descriptive information about PARS models. We intend for all review stages, citation screening, data extraction and risk of bias assessment to be conducted by at least two independent reviewers. As a broad spectrum of study designs, including randomised and non-randomised studies of interventions and mixed methods, will be eligible, we will use three separate tools to assess the risk of bias in individual studies. The data will be primarily synthesised narratively, following Intervention Component Analysis. If the data allow, we will perform a random-effects meta-analysis and meta-regression to investigate the impact of specific PARS components on effect sizes. Ethics and dissemination This systematic review does not require formal ethics approval. The results will be submitted to a peer-reviewed journal and international conferences to reach the scientific community. PROSPERO registration number CRD42021233229.
Keywords: physical activity referral scheme; physical activity prescription; exercise referral scheme

Position statement and updated international guideline for safe and effective whole-body electromyostimulation training-the need for common sense in WB-EMS application - Kemmler, Wolfgang; Fröhlich, Michael; Ludwig, Oliver; Eifler, Christoph; von Stengel, Simon; Willert, Sebastian; Teschler, Marc; Weißenfels, Anja; Kleinoeder, Heinz; Micke, Florian; Wirtz, Nicolas; Zinner, Christoph; et al. (Frontiers in Physiology, 2023)
Whole-Body Electromyostimulation (WB-EMS) is a training technology that enables simultaneous stimulation of all the main muscle groups with a specific impulse intensity for each electrode. The corresponding time-efficiency and joint-friendliness of WB-EMS may be particularly attractive for people unable or unmotivated to conduct (intense) conventional training protocols. However, due to the enormous metabolic and musculoskeletal impact of WB-EMS, particular attention must be paid to the application of this technology. In the past, several scientific and newspaper articles reported severe adverse effects of WB-EMS. To increase the safety of commercial non-medical WB-EMS application, recommendations "for safe and effective whole-body electromyostimulation" were launched in 2016. However, new developments and trends require an update of these recommendations to incorporate more international expertise with demonstrated experience in the application of WB-EMS. The new version of these consensus-based recommendations has been structured into 1) "general aspects of WB-EMS", 2) "preparation for training", recommendations for the 3) "WB-EMS application" itself and 4) "safety aspects during and after training". Key topics particularly addressed are 1) consistent and close supervision of WB-EMS application, 2) mandatory qualification of WB-EMS trainers, 3) anamnesis and corresponding consideration of contraindications prior to WB-EMS, 4) the participant's proper preparation for the session, 5) careful preparation of the WB-EMS novice, 6) appropriate regeneration periods between WB-EMS sessions and 7) continuous interaction between trainer and participant at a close physical distance. In summary, we are convinced that the present guideline will contribute to greater safety and effectiveness in the area of non-medical commercial WB-EMS application.
CRIS-Team WoS Importer:2023-05-05

Prevalence of sarcopenia and sarcopenic obesity in older German men using recognized definitions: high accordance but low overlap! - Kemmler, Wolfgang; Teschler, Marc; Weißenfels, Anja; Sieber, Cornel; Freiberger, Ellen; von Stengel, Simon (Osteoporosis international, 2017)
Keywords: Men; Prevalence; 70+; Germany; Sarcopenia; Sarcopenic obesity

Recommended Contraindications for the Use of Non-Medical WB-Electromyostimulation - Kemmler, Wolfgang; Weißenfels, Anja; Willert, Sebastian; Fröhlich, M.; Ludwig, O.; Berger, J.; Zart, S.; Becker, S.; Backfisch, M.; Kleinöder, H.; Dörmann, U.; Wirtz, N.; et al. (Deutsche Zeitschrift für Sportmedizin, 2019)
Rare but regularly recurring complications are leading to ongoing regulation of the commercial, non-medical whole-body electromyostimulation (WB-EMS) market. In addition to the revised German Radiation Protection Statutes (NiSV), the “Deutsche Industrie Norm” (DIN) 33961-5 was recently published with safety policies for WB-EMS application, anchoring both relative and absolute contraindications for WB-EMS for the first time. The purpose of this article is to justify the rationale of contraindications in a commercial setting and to support their consistent application. › While the relative contraindications appear plausible and uncritical, absolute contraindications for WB-EMS are much more debatable. In fact, some absolute contraindications (e.g. diabetes mellitus) could be safely addressed by WB-EMS at least after careful medical anamnesis and competent, close supervision. However, this requires sound knowledge of WB-EMS on the part of physicians and instructors, low user-trainer ratios and prompt medical care in an emergency. › However, considering the multitude of different settings of commercial WB-EMS, in extreme cases with hardly supervised, only video-guided WB-EMS sessions, the necessary accurateness and expertise for safe WB-EMS is not always guaranteed. That there is no mandatory licensing of WB-EMS instructors, the key players in WB-EMS, underscores the concern. › Whilst acknowledging the multitude of high-quality suppliers, it is advised that the commercial, non-medical WB-EMS sector as a whole to be wary of indications with significantly increased complication potential. Lastly, the mandatory acceptance of the contraindications listed in DIN 33961-5 might be considered as an inevitable step towards preventing overregulation by official authorities.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Commercial Application; DIN 33961-5; Guideline; Whole-Body Electromyostimulation

Schlüsselkomponenten von Bewegungsversorgungsketten: Eine systematische Übersichtsarbeit - Mino, Eriselda; Geidl, Wolfgang; Hanson, Coral; Mchale, Sheona; Naber, Inga; Weißenfels, Anja; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Jahrestagung dvs-Kommission Gesundheit, 2022)
Einleitung In vielen Ländern sind Bewegungsversorgungsketten (BVK) zur Förderung der körperlichen Aktivität (KA) etabliert. BVK beginnen meist bei medizinischem Fachpersonal, welches den Patientinnen und Patienten eigenständige KA oder ein betreutes Bewegungsförderungsprogramm verschreibt. BVK können jedoch auch deutlich komplexer sein und variieren dabei hinsichtlich ihrer Merkmale und Interventionskomponenten. Das Ziel dieser Arbeit ist eine systematische Übersicht der Schlüsselkomponenten von BVK (vgl. Mino et al. 2021). Methode Es wurde eine systematische Suche nach Artikeln in verschiedenen Datenbanken (u.a. Pub-Med, Scopus) durchgeführt (bis April 2022). Eingeschlossen wurden (quasi-)experimentelle, prospektive, qualitative und Mixed-Methods-Studien, die BVK für inaktive Menschen mit vorhandenen nichtübertragbaren Erkrankungen oder assoziierten Risikofaktoren untersuchen. In der Volltextanalyse wurden Programmaufnahme und -adhärenz sowie Änderungen der KA extrahiert; weiterhin wurden mittels Interventionskomponentenanalyse (Sutcliffe et al. 2015) und einer Checkliste (Hanson et al. 2020) Strukturen und Inhalte der BVK analysiert. Ergebnisse Die Suche ergab 4893 Studien von denen 54 eingeschlossen wurden. Daten zur KA wurden von 43 Studien erhoben, 37 Studien berichteten Programmaufnahme oder –adhärenz. Die häufigsten Schlüsselkomponenten der Ketten sind ein patientenzentrierter Ansatz, Individualisierung, Screening, Eingangs- und Ausgangsassessment, motivierende Beratungen, Kurzberatung, Verschreibung oder Überweisung, betreutes oder unbeaufsichtigtes Trainingsprogramm, strukturierte Nachbereitung und Nachsorgestrategien. Diskussion Diese Arbeit bietet einen internationalen Überblick der Schlüsselkomponenten von BVK. Im nächsten Schritt werden die einzelnen Interventionskomponenten bezüglich ihrer Wirksamkeit für Bewegungsförderung, Programmaufnahme und –adhärenz analysiert. Die Ergebnisse liefern wichtige Informationen für die Ausgestaltungsmöglichkeiten von BVK. Literatur Mino E, Geidl W, Naber I, et al. Physical activity referral scheme components: a study protocol for systematic review and meta-regression. BMJ Open 2021;11(e049549). Sutcliffe K, Thomas J, Stokes G, et al. Intervention component analysis (ICA): a pragmatic approach for identifying the critical features of complex interventions. Syst Rev 2015;4:140. Hanson CL, Oliver EJ, Dodd-Reynolds CJ, et al. A modified Delphi study to gain consensus for a taxonomy to report and classify physical activity referral schemes (pars). Int J Behav Nutr Phys Act 2020;17:158.
Keywords: Bewegungsförderung; Versorgung; Bewegungsversorgungskette

Short-time effect of a single session of intense whole-body electromyostimulation on energy expenditure. A contribution to fat reduction? - Teschler, Marc; Wassermann, Alfred; Weißenfels, Anja; Froehlich, Michael; Kohl, Matthias; Bebenek, Michael; von Stengel, Simon; Kemmler, Wolfgang (Applied Physiology Nutrition and Metabolism-Physiologie Appliquee Nutrition Et Metabolisme, 2017)
To determine the underlying mechanisms after one session of (intense) whole-body electromyostimulation (WB-EMS) on total energy expenditure (TEE) and resting metabolic rate (RMR), 16 subjects followed a standardized protocol of indirect calorimetry for up to 72h in 12h intervals. The single session significantly increased RMR about 25±10% (p<0.001) and TEE for about 9.5±1%, a net effect of 460±50 kcal (WB-EMS vs. CG).
EVALuna2:33278

Similar Pain Intensity Reductions and Trunk Strength Improvements Following Whole-Body Electromyostimulation vs. Whole-Body Vibration vs. Conventional Back-Strengthening Training in Chronic Non-specific Low Back Pain Patients: A Three-Armed Randomized Controlled Trial - Micke, Florian; Weißenfels, Anja; Wirtz, Nicolas; von Stengel, Simon; Doermann, Ulrike; Kohl, Matthias; Kleinoeder, Heinz; Donath, Lars; Kemmler, Wolfgang (Frontiers in Physiology, 2021)
The aim of this multicenter trial was to compare the effects of whole-body electromyostimulation (WB-EMS) and whole-body vibration (WBV) with conventional back-strengthening training (CT) on changes in mean back pain intensity (MPI) and trunk strength in patients suffering from chronic non-specific low back pain (CNLBP). Two-hundred and forty CNLBP patients (40–70 years; 62% female) were randomly assigned to three intervention arms (WB-EMS: n = 80 vs. WBV: n = 80 vs. CT: n = 80). All training intervention programs were performed for 12 weeks in their usual commercial training setting. Before and during the last 4 weeks of the intervention, MPI was recorded using a 4-week pain diary. Additionally, maximal isometric trunk extension and -flexion strength was assessed on the BackCheck® machine. A moderate but significant decrease of MPI was observed in all groups (WB-EMS: 29.7 ± 39.1% (SMD 0.50) vs. WBV: 30.3 ± 39.3% (SMD 0.57) vs. CT: 30.5 ± 39.6% (SMD 0.59); p < 0.001). Similar findings were observed for maximal isometric strength parameters with a significant increase in all groups (extension: WB-EMS: 17.1 ± 25.5% vs. WBV: 16.2 ± 23.6% vs. CT: 21.6 ± 27.5%; p < 0.001; flexion: WB-EMS: 13.3 ± 25.6% vs. WBV: 13.9 ± 24.0% vs. CT: 13.9 ± 25.4%; p < 0.001). No significant interaction effects for MPI (p = 0.920) and strength parameters (extension: p = 0.436; flexion: p = 0.937) were observed. WB-EMS, WBV, and CT are comparably effective in improving MPI and trunk strength. However, training volume of WB-EMS was 43 or 62% lower, compared with CT and WBV.
CRIS-Team Scopus Importer:2021-05-14
Keywords: electrical stimulation; lumbar spine pain; MVC; strength training; vibration training

The association of physical activity referral scheme’ components with physical activity level, scheme uptake and adherence rates: a systematic review, meta-analysis with meta-regression - Geidl, Wolfgang; Brandmeier, Anna; Klamroth, Sarah; Naber, Inga; Weißenfels, Anja; Abu-Omar, Karim; Pfeifer, Klaus; Mino, Eriselda; Hanson, Coral L.; Mchale, Sheona; Schuler, Michael; Gelius, Peter; et al. (Proceedings of the 15th conference of HEPA Europe "Optimising health enhancing physical activity: the importance of inclusion", 2024)
Purpose Physical activity referral schemes (PARS) are complex interventions comprised of multiple components such as screening, brief advice, and written prescription. This study aimed to investigate the relationship between PARS components and physical activity, uptake, and adherence rates. Additionally, the overall effect of PARS is analysed. Methods 6 databases were searched for studies published between 1990-2023; included PARS with participants ≥16 years old; and reported either physical activity, uptake or adherence outcomes. GRADE was used to assess quality of evidence. Separate random-effects meta-analysis by comparison group were conducted for physical activity. Uptake and adherence rates were pooled using proportional meta-analysis. The PARS components were analyzed via univariate meta-regression. Results We included 52 studies from which 50 targeted people with, or at risk of, non-communicable diseases. PARS were compared with usual care (11 RCTs, Hedges’ g = 0.18, 95%CI 0.12 to 0.25), physical activity advice (5 RCTs, Hedges’ g=-0.6, 95%CI -0.21 to 0.10), or enhanced PARS (9 RCTs, Hedges’ g = 0.07, 95%CI -0.03 to 0.18). The pooled uptake rate was 87% (95%CI 77% to 94%) among 14 RCTs and 68% (95%CI 51% to 83%) among 14 non-experimental studies. The adherence rate across 16 RCTs and 18 non-experimental studies was 68% (95%CI 55% to 80%) and 53% (95%CI 42% to 63%) respectively. The meta-regression showed that PARS incorporating a person-centered approach, screening, and brief advice had higher adherence rates. In contrast, PARS offering physical activity sessions had lower adherence rates. No other component-outcome relationship reached statistical significance. Conclusion High certainty of evidence confirms a small effect of PARS in increasing physical activity compared to usual care. The evidence comparing PARS with advice and enhance scheme versions is inconclusive and comes from low certainty of evidence. Four out of the 19 PARS components may predict adherence. Practical implications The results improve our understanding of effective PARS components in relation to physical activity promotion, scheme uptake and adherence and thus support the future development of optimal PARS. Funding The study was conducted within the project BewegtVersorgt, which is funded by the Federal Ministry of Health based on a resolution of the German ‘Bundestag’ by the federal government.
Keywords: physical activity referral scheme; physical activity

The Impact of Baseline Pain Intensity on the Effectiveness of Whole-Body Electromyostimulation (WB-EMS) for Nonspecific Chronic Back Pain. - Konrad, Karl L.; Weißenfels, Anja; Birkenmaier, Christof; Baeyens, Jean-Pierre; Kemmler, Wolfgang; Wegener, Bernd (Cureus, 2024)
INTRODUCTION: Recent clinical studies confirmed that whole-body electromyostimulation (WB-EMS) training is a safe and time-efficient therapeutic method for patients with nonspecific chronic back pain (NSCBP). However, significant variations in initial pain intensity among subjects in these studies have been observed. This study aims to determine if patients with differing initial pain intensities experience varying degrees of benefit from WB-EMS and to assess the overall correlation between initial pain levels and pain reduction. METHODS: Pain intensity datasets from two studies were combined. The pooled data included 121 NSCBP patients (38 males and 83 females) with an average age of 55.1 years (±11.8 years). Data was categorized by baseline pain intensity on the numeric rating scale (NRS) into seven groups: 0 to 2, >2 to 3, >3 to 4, >4 to 5, >5 to 6, >6 to 7, and >7. Both absolute and relative changes were analyzed. Additionally, a Spearman rho correlation test was performed on the entire dataset to evaluate the relationship between initial pain level and pain reduction. RESULTS: Significant improvements were noted across all NRS11 categories, with strong effect sizes (p) in all classes above 2, ranging from 0.56 to 0.90. The >7 category exhibited the highest rate of clinically significant changes (80%) and an average improvement of 3.72 points. The overall group from >1 to 10 showed an average improvement of 1.33 points, with 37% of the participants experiencing clinically significant improvements. The Spearman rho correlation test revealed a moderate positive relationship between initial pain level and pain reduction (r_s = 0.531, p < 0.001), indicating that, generally, higher initial pain levels are associated with greater pain reduction. CONCLUSION: The findings support the hypothesis that NSCBP patients with higher baseline NRS values benefit more substantially from WB-EMS. Those with NRS values above 7 show the greatest improvement and highest rate of clinical significance. The overall positive correlation between initial pain intensity and pain reduction further underscores the efficacy of WB-EMS in managing NSCBP across different pain intensities.
EVALuna2:571032

Überprüfung einer entwickelten Versorgungsstruktur zur Bewegungsförderung für Menschen mit nichtübertragbaren Erkrankungen – Protokoll über eine pragmatische Studie im Cluster-Design - Weißenfels, Anja; Mino, Eriselda; Naber, Inga; Klamroth, Sarah; Gelius, Peter; Geidl, Wolfgang; Abu-Omar, Karim; Pfeifer, Klaus (20. Deutscher Kongress für Versorgungsforschung, 2021)

Whole-body electromyostimulation and protein supplementation favorably affect sarcopenic obesity in community-dwelling older men at risk: the randomized controlled FranSO study - Kemmler, Wolfgang; Weißenfels, Anja; Teschler, Marc; Willert, Sebastian; Bebenek, Michael; Shojaa, Mahdieh; Kohl, Matthias; Freiberger, Ellen; Sieber, Cornel; von Stengel, Simon (Clinical Interventions in Aging, 2017)
Background: Sarcopenic obesity (SO) is a geriatric syndrome characterized by the disproportion between the amount of lean mass and fat mass. Exercise decreases fat and maintains muscle mass; however, older people fail to exercise at doses sufficient to affect musculoskeletal and cardiometabolic risk factors. The aim of this study was to evaluate the effect of whole-body electromyostimulation (WB-EMS), a time-efficient, joint-friendly and highly individualized exercise technology, on sarcopenia and SO in older men.Materials and methods: A total of 100 community-dwelling northern Bavarian men aged >= 70 years with sarcopenia and obesity were randomly (1-1-1) assigned to either 16 weeks of 1) WB-EMS and protein supplementation (WB-EMS&P), 2) isolated protein supplementation or 3) nonintervention control. WB-EMS consisted of 1.5x20 min (85 Hz, 350 mu s, 4 s of strain to 4 s of rest) applied with moderate-to-high intensity while moving. We further generated a daily protein intake of 1.7-1.8 g/kg/body mass per day. The primary study end point was Sarcopenia Z-Score, and the secondary study end points were body fat rate (%), skeletal muscle mass index (SMI) and handgrip strength.Results: Intention-to-treat analysis determined a significantly favorable effect of WB-EMS&P (P < 0.001) and protein (P=0.007) vs control. Both groups significantly (P < 0.001) lost body fat (WB-EMS&P: 2.1%; protein: 1.1%) and differed significantly (P<0.004) from control (0.3%). Differences between WB-EMS&P and protein were significant for the Sarcopenia Z-Score (P=0.39) and borderline nonsignificant (P=0.051) for body fat. SMI increased significantly in both groups (P, 0.001 and P=0.043) and decreased significantly in the control group (CG; P=0.033); differences between the verum groups and control were significant (P <= 0.009). Handgrip strength increased in the WB-EMS group (1.90 kg; P < 0.001; P=0.050 vs control) only. No adverse effects of WB-EMS or protein supplementation were recorded.Conclusion: WB-EMS&P is a safe and efficient method for tackling sarcopenia and SO in older men. However, the suboptimum effect on functional parameters should be addressed by increased voluntary activation during WB-EMS application.
EVALuna2:33281
Keywords: sarcopenia; sarcopenic obesity; exercise; electrostimulation; older people

Whole-body electromyostimulation to fight sarcopenic obesity in community-dwelling older women at risk. Results of the randomized controlled FORMOsA-sarcopenic obesity study - Kemmler, Wolfgang; Teschler, Marc; Weißenfels, Anja; Bebenek, Michael; von Stengel, Simon; Kohl, Matthias; Freiberger, Ellen; Goisser, Sabine; Jakob, F.; Sieber, Cornel; Engelke, Klaus (Osteoporosis international, 2016)
The effect of whole body-electromyostimulation in community-dwelling women >= 70 with sarcopenic obesity was heterogeneous, with high effects on muscle mass, moderate effects on functional parameters, and minor effects on fat mass. Further, we failed to determine a supportive effect of additional protein-enriched dietary supplementation in this albeit predominately well-nourished group.Introduction The aim of the study was to determine the effect of whole-body electromyostimulation (WB-EMS) on sarcopenic obesity (SO) in community-dwelling women more than 70 years with sarcopenic obesity.Methods Seventy-five community-dwelling women >= 70 years with SO were randomly allocated to either a WB-EMS application with (WB-EMS & P; 24.9 +/- 1.9 kg/m(2)) or without (WB-EMS; 25.2 +/- 1.8 kg/m(2)) dietary supplementation (150 kcal/day, 56 % protein) or a non-training control group (CG; 24.7 +/- 1.4 kg/m(2)). WB-EMS consisted of one weekly session of 20 min (85 Hz, 350 mu s, 4 s of strain-4 s of rest) performed with moderate to high intensity. Primary study endpoint was the Sarcopenia Z-Score constituted by skeletal muscle mass index (SMI, as assessed by dual energy X-ray absorptiometry), grip strength, and gait speed, and secondary study endpoint was body fat (%).Results Sarcopenia Z-score comparably increases in the WB-EMS and the WB-EMS&P-group (p=.046). Both groups differ significantly (p=.001) from the CG which deteriorated significantly (p=.006). Although body fat changes were most pronounced in the WB-EMS (-0.9 +/- 2.1; p=.125) and WB-EMS&P (-1.4 +/- 2.5; p=.028), reductions did not statistically differ (p=.746) from the CG (-0.8 +/- 2.7; p=.179). Looking behind the covariates, the most prominent changes were determined for SMI, with a significant increase in both EMS-groups (2.0-2.5 %; p=.003) and a decrease in the CG (-1.2 +/- 3.1 %; p=.050) with significant between-group differences (p=.001).Conclusion WB-EMS is a safe and attractive method for increasing muscle mass and functional capacity in this cohort of women 70+ with SO; however, the effect on body fat is minor. Protein-enriched supplements did not increase effects of WB-EMS alone.
EVALuna2:33286
Keywords: Body fat; Community-dwelling older people; Sarcopenic obesity; Skeletal muscle mass; Whole-body electromyostimulation

Zur Rolle des Bewegungsfachberufs in internationalen Bewegungsversorgungsstrukturen - ein internationaler Vergleich - Weißenfels, Anja; Naber, Inga; Mino, Eriselda; Klamroth, Sarah; Geidl, Wolfgang; Abu-Omar, Karim; Pfeifer, Klaus (Bewegungstherapie und Gesundheitssport, 2020)
Aufgrund einer zunehmenden körperlichen Inaktivität der Weltbevölkerung haben durch Bewegungsmangel induzierte Erkrankungen in den letzten Jahren stark zugenommen. Nicht nur zur Prävention nichtübertragbarer Erkrankungen (noncommunicable diseases: NCD), sondern auch aus rehabilitativer Perspektive ist regelmäßige körperliche Aktivität ein essenzieller Gesundheitsfaktor und eine Ergänzung oder Alternative zur medikamentösen Behandlung. Ärztlich initiierte Bewegungsversorgung ist in vielen Ländern bereits in den jeweiligen Gesundheitssystemen etabliert, während die deutsche Regelversorgung hier bislang noch Defizite aufweist. Die Bewegungsversorgungsmodelle aus Schweden, Dänemark und Neuseeland zeigen deutliche Stärken bei der interdisziplinären Zusammenarbeit unterschiedlicher Berufsgruppen (Ärzt*innen, Bewegungsfachberufe) sowie der Integration verhaltensbezogener Bewegungsförderung. Personen aus Bewegungsfachberufen (u. a. Physio-, Bewegungs- und Sporttherapeut*innen) haben international eine einflussreiche Rolle bei der individuellen Verhaltensänderung zur Steigerung körperlicher Aktivität, und im Vergleich zum deutschen System ist das Aufgabengebiet dieser Berufsgruppe bedeutsam erweitert. International betrachtet setzen Bewegungsfachberufe regelhaft theoriebezogene Inhalte der Bewegungsförderung ein, wie z. B. motivationale Gesprächsführung (MI) oder auch Follow-up-Telefonanrufe, und sind teilweise sogar befugt, Bewegungsrezepte auszustellen. Der systematische Einsatz von Inhalten zur Bewegungsförderung durch Bewegungsfachberufe und die gezielte interdisziplinäre Zusammenarbeit mit Ärzt*innen werden im hiesigen Gesundheitssystem bislang kaum oder nur rudimentär verfolgt, weshalb das Projekt BewegtVersorgt neben der Etablierung einer wirkungsvollen Bewegungsversorgungskette besonders das Aufgabengebiet der Bewegungsfachberufe in den Fokus nimm
Keywords: Körperliche Aktivität; ärztlich initiierte Bewegungsförderung; Bewegungsversorgungsketten; nichtübertragbare Erkrankungen; Primärversorgung